MASİF KEMİK DESTRÜKSİYONU İLE SEYREDEN MALİGN GLOMUS JUGULARE PARAGANGLİOMASI: OLGU SUNUMU - TÜZGEN, Saffet; TANRIÖVER, Necmettin; CANBAZ, Bülent; ÖZYURT, Emin; KUDAY, Cengiz (Cerrahpaşa Medical Journal, 2014)
Background.- Glomus jugulare paragangliomas are uncommon, hypervascular neoplasms that arise from the temporal paraganglia and typically display a benign histology. Bone changes, including bony destruction, within or around the tumor is extremely rare. These tumors rarely display clinical or histological malignant characteristics with a commonly cited figure of only 5% in the literature. Observation.- We present a review of the literature of glomus jugulare paragangliomas and report a case with massive bony destruction in the temporal and occipital bones, secondary to a hypervascular glomus jugulare tumor. Embolization of the feeding arteries was carried out prior to total resection and finally a histological diagnosis of malignant glomus jugulare paraganglioma was made.